1986
DOI: 10.1177/000992288602500109
|View full text |Cite
|
Sign up to set email alerts
|

Pertussis Complicated by the Syndrome of Inappropriate Antidiuretic Hormone Secretion

Abstract: Two cases of pertussis complicated by the syndrome of inappropriate antidiuretic hormone secretion (SIADH) are reported. Both patients experienced seizures associated with hyponatremia. Patients with severe pertussis are at risk for SIADH and should be monitored closely for its development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…[12][13][14] Experimental and clinical observations have suggested that hypoxaemia and hypercapnia stimulate release of antidiuretic hormone. "In this study a large number of patients with a PaCO2 above 5-33 kPa, which can be considered as pathologically increased if tachypnoea is present, had raised antidiuretic hormone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Experimental and clinical observations have suggested that hypoxaemia and hypercapnia stimulate release of antidiuretic hormone. "In this study a large number of patients with a PaCO2 above 5-33 kPa, which can be considered as pathologically increased if tachypnoea is present, had raised antidiuretic hormone concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The complication and indeed, a red herring in this case, of hyponatraemia has been mentioned in childhood cases secondary to SIADH,8 related to neonatal oedema9 or related to cerebral haemorrhages, disseminated intravascular coagulation and concomitant pseudomonas infection 10…”
Section: Discussionmentioning
confidence: 55%
“…However, there has been only 1 report describing pertussis complicated with SIADH, 4 indicating that this might be a comparatively rare state. Although our case showed the atypical clinical course as pertussis, lacking the symptoms of apnea, whooping cough, and laboratory data of hyperleukocytosis especially in lymphocytes, these symptoms indicate the diagnosis in most pertussis patients and let us make early medical interventions especially in infants, resulting in the avoidance of severe complications such as pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, there are few reports describing any association with pertussis. 4 We report on the case of a 6-week-old male infant exhibiting pertussis pneumonia with convulsive status associated with hyponatremia caused by SIADH.…”
mentioning
confidence: 99%
See 1 more Smart Citation